2020
DOI: 10.1002/alr.22680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and reversibility of smell dysfunction measured psychophysically in a cohort of COVID‐19 patients

Abstract: Background Considerable evidence suggests that smell dysfunction is common in coronavirus disease-COVID-Unfortunately extant data on prevalence and reversibility over time are highly variable coming mainly from self-report surveys prone to multiple biases Thus validated psychophysical olfactory testing is sorely needed to establish such parameters Methods One hundred severe acute respiratory syndrome-coronavirus-SARS-CoV-positive patients were administered the-item University of Pennsylvania Smell Identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
124
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 37 publications
6
124
2
1
Order By: Relevance
“…The lack of significant associations between olfactory scores otolaryngological symptoms was found in many previous studies [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 52 ], supporting the hypothesis that COVID-19 olfactory disturbances are not related to rhinitis (i.e., nasal obstruction, rhinorrhea, post-nasal drip) but are probably neurological. This peculiarity, combined with the fact that this chemosensitive disorder represents the presenting symptom of COVID-19 in 29.3% of cases [ Table 3 ], makes olfactory dysfunctions the key symptom in the differential diagnosis between COVID-19 and common flu [ 36 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The lack of significant associations between olfactory scores otolaryngological symptoms was found in many previous studies [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 52 ], supporting the hypothesis that COVID-19 olfactory disturbances are not related to rhinitis (i.e., nasal obstruction, rhinorrhea, post-nasal drip) but are probably neurological. This peculiarity, combined with the fact that this chemosensitive disorder represents the presenting symptom of COVID-19 in 29.3% of cases [ Table 3 ], makes olfactory dysfunctions the key symptom in the differential diagnosis between COVID-19 and common flu [ 36 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 81%
“…The realization of objective olfactory assessments of these patients was difficult during the pandemic as a result of the sanitary recommendation of avoiding the endonasal examination, the home-management of many patients in quarantine, and therefore, the inability to perform psychophysical testing [ 14 ]. To date, only a few objective studies have been conducted on small case series, thus reliable conclusions are limited [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, the objective olfactory assessment with validated, repeatable, and standardized tests remains crucial to confirm, characterize, and follow the OD over time.…”
Section: Introductionmentioning
confidence: 99%
“…By using University of Pennsylvania Identification Tests (UPSIT), Moein, Hashemian, Tabarsi, et al (2020) reported some degree of smell loss in 96% of their tested COVID-19 participants. The differences between studies using objective methods could stem from the relative smaller sample size (as in our case) and the different timing of testing during the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between studies using objective methods could stem from the relative smaller sample size (as in our case) and the different timing of testing during the disease progression. Indeed, in our work, we tested at around 20 days since disease onset compared with shorter onset in other studies ( Bocksberger et al 2020 ; Moein, Hashemian, Tabarsi, et al 2020 ; Tsivgoulis et al 2020 ; Vaira, Hopkins, et al 2020 ). Despite the delayed timing of our tests, our anosmic participants were around 10%, similar to the 8% reported by Le Bon et al (2020) who tested their participants 5 weeks after the onset of olfactory loss and more or less 15 days after their confirmed COVID-19 diagnosis obtained either by RT-PCR on nasopharyngeal swab or by serology testing.…”
Section: Discussionmentioning
confidence: 99%
“…This is why differing ratios are reported in different series. Also, data associated with the progression of olfactory dysfunctions are limited in the literature [ 11 16 ]. The purpose of the present study is to test the olfactory dysfunctions that occur in the course of COVID-19 with BSIT and to disclose its progress by time.…”
Section: Introductionmentioning
confidence: 99%